Stereoacuity and ocular-associated factors in children aged 3–7 years in Guangxi, Southwest China: a cross-sectional study - Xiao, Xin; Huang, Huiyao; Luo, Yan; Luo, Wuqiang; Li, Lili; Lin, Enwei; Kong, Min; Chen, Qi (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the distribution of stereoacuity and its ocular-associated factors in children aged 3–7 years in Guangxi, Southwest China.MethodsThis cross-sectional study recruited 4,090 children aged 3–7 years (mean: 5.12 ± 0.95 years) from 12 randomly selected kindergartens via cluster sampling in Nanning City, Guangxi, Southwest China. Comprehensive ocular assessments included visual acuity assessment, cover/uncover and alternating cover tests, anterior segment examination, fundus examination, the Titmus stereo test, and cycloplegic autorefraction. The univariate and multivariate logistic regression models were used to determine the factors associated with subnormal stereoacuity (>40 arcsec).ResultsThe prevalence rates of anisometropia, astigmatism, and strabismus were 18.24, 26.11, and 0.20%, respectively. The mean stereoacuity was 1.88 ± 0.34 log units (median: 60.25 arcsec), with the majority (65.18%) having subnormal stereoacuity. The mean log units of stereoacuity decreased with age (F = 144.7, p < 0.001). Compared to girls, boys had a significantly greater mean log unit stereoacuity (1.90 ± 0.35 vs. 1.87 ± 0.34, t = 2.589, p = 0.010). In the multivariate logistic regression, older age (odds ratio [OR]: 0.040–0.461 for years 4–7, 95% confidence interval [CI]: 0.018–0.613 for years 4–7, all p < 0.001) and girls (OR = 0.672, 95% CI: 0.584–0.772, p < 0.001) were protective factors, whereas interocular acuity difference [IAD] (OR = 6.906, 95% CI: 3.133–16.01, p < 0.001), mean LogMAR acuity (OR = 11.491, 95% CI: 6.065–22.153, p < 0.001), mean cylindrical error [CYLmean] (OR = 1.201, 95% CI: 1.055–1.365, p = 0.005), and anisometropia (OR = 1.452, 95% CI: 1.202–1.760, p < 0.001) were risk factors for subnormal stereoacuity.ConclusionOcular factors, including higher IAD, worse acuity, greater astigmatism, and greater anisometropia, were identified as risk factors for subnormal stereoacuity, highlighting the importance and urgency of early screening for stereoacuity and ocular risk factors in children aged 3–7 years in Guangxi.